Type E coronary artery dissection caused by intravascular lithotripsy balloon rupture; vessel anatomy and characteristics in a lithoplasty complication case as detailed by optical coherence tomography: a case report. Issue 12 (23rd October 2021) - Lee, Tjen Jhung; Wan Rahimi, Wan Faizal Bin; Low, Ming Yoong; Nurruddin, Amin Ariff
Abstract: Background: Intravascular lithotripsy is a new method used to treat calcified coronary lesions (CCLs). Percutaneous coronary intervention of CCLs has conventionally been classified as a complex procedure. In the majority of calcified cases, atherectomy is required for sufficient plaque modification prior to stent implantation. Intravascular lithotripsy has been shown to be safe and effective in clinical trials, but as worldwide usage increases, cases of complications are beginning to emerge. Case summary: We describe a 71-year-old woman, who after an episode of non-ST-elevation acute coronary syndrome underwent coronary angiography. The culprit vessel was identified to be a severely stenosed left anterior descending artery which was also heavily calcified and tortuous. Intravascular lithotripsy (IVL) was employed for calcium modification prior to stent implantation, but the IVL balloon ruptured during shockwave lithotripsy, resulting in coronary artery dissection. Subsequent management steps and stent deployment resulted in favourable angiographic results. Our findings are further detailed on optical coherence tomography, demonstrating certain features which might predispose to IVL balloon rupture. Discussion: We discuss the mechanism of action during intravascular lithotripsy, and how the shockwaves from the lithotripter modify calcified lesions, whilst keeping soft tissue unharmed. Results from clinical trials and multiple real-world studies have shown that complication rates are low. This case report aims to illustrate how the rupture of an intravascular lithotripsy balloon can result in coronary artery dissection. Optical coherence tomography can help in identifying potential anatomical features which may precede such complications.